2020
DOI: 10.24843/jbiounud.2020.v24.i02.p09
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Bacillus cereus dalam produksi biosurfaktan

Abstract: Biosurfaktan dari mikroorganisme mempunyai sifat fisika kimia yang stabil, tidak mencemari lingkungan, mudah terurai, dapat diperbaharui, lebih murah dan memiliki toksisitas rendah sehingga dapat digunakan dalam industri farmasi sebagai antibakteri. Penelitian ini bertujuan menguji aktivitas emulsifikasi dan karakterisasi biosurfaktan dari  Bacillus cereus. Uji hemolisis dan oli spreading dilakukan sebagai penapisan awal. Produksi biosurfaktan menggunakan sistem bacth yang dishaker selama 7 hari. Supernatan di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…The mechanism that causes hemolysis by biosurfactant compounds can be in the form of normal membrane dissolution at high biosurfactant concentrations or increased membrane permeability to small solutes at low biosurfactant concentrations, resulting in osmotic lysis (Setiani et al 2020). Biosurfactants have the property of surfactants to lyse cells by inducing membrane reorganization and causing changes in cell morphology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism that causes hemolysis by biosurfactant compounds can be in the form of normal membrane dissolution at high biosurfactant concentrations or increased membrane permeability to small solutes at low biosurfactant concentrations, resulting in osmotic lysis (Setiani et al 2020). Biosurfactants have the property of surfactants to lyse cells by inducing membrane reorganization and causing changes in cell morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Biosurfactants that have an emulsification index value of >30% in the screening stage are considered positive for having significant emulsification activity (Shoeb et al 2015). The interface emulsification ability of biosurfactants is influenced by their structure, components, and amphiphilic properties (Setiani et al 2020;Durval et al 2021). Nor et al (2023) reported that the Bacillus cereus KH1 cell-free supernatant emulsified with palm oil produced the largest emulsification index of 67% compared to other oils and hydrocarbons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates the presence of biosurfactant compounds which belong to the lipopeptide group. The presence of spots that are not completely round in shape indicates that the biosurfactant compound is not yet pure and is still in the form of a crude extract so further purification is needed [17].…”
Section: Thin Layer Chromatography (Tlc)mentioning
confidence: 99%
“…Pemberian probiotik Bacillus cereus dapat mempertahankan jumlah eritrosit pada ternak [28]. Bacillus cereus merupakan bakteri gram positif yang menguntungkan bagi inangnya (29). Bacillus cereus menghasilkan enzim protease untuk mengubah protein menjadi asam amino yang dibutuhkan dalam proses pembentukan darah (30).…”
Section: Jumlah Eritrositunclassified